THE URGENCY OF ASSET CONFISCATION WITHOUT CRIMINAL PROSECUTION IN CORRUPTION CRIMES AS RENEWAL OF INDONESIAN CRIMINAL LAW - Hidayat, Ahmad Arif; Karim, Muhammad Said (Al-Risalah, 2023)
The Urgency of Confiscation of Assets Without Criminal Prosecution of Corruption for a Country of Confiscation of Assets without Criminal Prosecution of Corruption can be Implemented in Indonesia. Research using normative legal research. Is a legal research method that combines a normative legal approach, namely statutory law and a conceptual approach'. The results of the study showed that (1) Mechanisms for appropriation of assets without prosecution for corruption. The process is more effective because it bypasses several legal principles and also by lowering the standard of proof in criminal cases, is considered to have the potential to face the principle of a fair trial (due process of law). as well as the right to own one's property (property rights). This is, for example, reflecting on the experience of lawsuits for judicial review of several articles in the TPPU Law, such as the matter of reverse proof and evidence of predicate crimes. Even though the Constitutional Court Decision has confirmed the constitutionality of the articles being tested, (2) The biggest challenge for introducing the in rem asset confiscation law in the Asset Confiscation Bill is how to explain this approach, which separates the relationship of assets proceeds of crime from the perpetrators of crimes. Even though it is not at all aimed at eliminating the criminal justice process, sometimes in rem deprivation will only be after the proceeds of crime without regard to who the perpetrators are.